Algorithms and Architectures for Parallel Processing 16th International Conference, ICA3PP 2016, Granada, Spain, December 14-16, 2016, Proceedings - Carretero, Jesus; Garcia-Blas, Javier; Ko, Ryan K.L; Mueller, Peter; Nakano, Koji (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 16th International Conference on Algorithms and Architectures for Parallel Processing, ICA3PP 2016, held in Granada, Spain, in December 2016. The 30 full papers and 22 short papers presented were carefully reviewed and selected from 117 submissions. They cover many dimensions of parallel algorithms and architectures, encompassing fundamental theoretical approaches, practical experimental projects, and commercial components and systems trying to push beyond the limits of existing technologies, including experimental efforts, innovative systems, and investigations that identify weaknesses in existing parallel processing technology.